2003
DOI: 10.1091/mbc.02-05-0074
|View full text |Cite
|
Sign up to set email alerts
|

Human MPS1 Kinase Is Required for Mitotic Arrest Induced by the Loss of CENP-E from Kinetochores

Abstract: We have determined that the previously identified dual-specificity protein kinase TTK is the human orthologue of the yeast MPS1 kinase. Yeast MPS1 (monopolar spindle) is required for spindle pole duplication and the spindle checkpoint. Consistent with the recently identified vertebrate MPS1 homologues, we found that hMPS1 is localized to centrosomes and kinetochores. In addition, hMPS1 is part of a growing list of kinetochore proteins that are localized to nuclear pores. hMPS1 is required by cells to arrest in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

28
178
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(208 citation statements)
references
References 68 publications
28
178
2
Order By: Relevance
“…of mitotic cells, which is consistent with the outcome from an immunoflourescence study recently reported by Liu et al [26].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…of mitotic cells, which is consistent with the outcome from an immunoflourescence study recently reported by Liu et al [26].…”
supporting
confidence: 92%
“…The centrosomal TTK may regulate spindle integrity and dynamics via phosphorylation of MAPs or other proteins involved in centrosomal duplication. During the preparation of this study, Liu et al (2003) have reported that human MPS1 is located at nuclear pore of interphase nucleus and to kinetochore and centrosome of mitotic cells [26]. Given the fact that the temporal order of dissociation of TTK from the kinetochore is correlated with the dephosphorylation profile of TTK reported by Liu et al [26], it is then possible that the phosphorylation of TTK may account for its function at the kinetochore.…”
Section: Ttk Is No Longer Associated With Kinetochore After Sister Chmentioning
confidence: 80%
“…It remains unclear whether the SAC component, Mps1p, also plays a role in centrosome duplication in higher eukaryotes [Fischer et al, 2004;Fisk et al, 2003;Liu et al, 2003;Stucke et al, 2004;Stucke et al, 2002] as it does in budding [Winey et al, 1991] but not in fission yeast [He et al, 1998]. The mammalian Ndc80p complex [McCleland et al, 2003], the ROD and ZW10 kinetochore proteins [Basto et al, 2000;Chan et al, 2000], the outer kinetochore protein Zwint-1 [Obuse et al, 2004;Wang et al, 2004a], and the kinetochore-associated NEK2A protein [Lou et al, 2004] are also required for the spindle checkpoint, indicating that the kinetochore's role in SAC signaling is evolutionarily conserved, although no ROD, ZW10, or Zwint-1 homologues have been identified in yeast.…”
Section: Higher Eukaryotesmentioning
confidence: 99%
“…Overexpression of Mps1 in yeast is sufficient to activate the spindle checkpoint and arrests cells in mitosis in the absence of spindle damage (8). Subsequent studies then identified orthologs of Mps1 in various organisms, revealing that the function of Mps1 in the spindle checkpoint is conserved from yeast to man (9)(10)(11)(12). In addition, Mps1 has meiotic and developmental functions in multicellular organisms, such as fly and zebra fish (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%